Factors affecting the management of the Ming Dynasty textile industry, People’s Republic of China - Yingjie, Han; Vanichwattananuwat, Chaiyot (Journal of Humanities and Social Sciences Review, 2024)
The objectives of this research were 1) to collect information on the management of Ming Dynasty textiles in the People’s Republic of China 2) to analyze factors affecting the management of the Ming Dynasty textile industry in the People’s Republic of China. This research is qualitative and the research instrument was an interview form with a sample of 6 people consisting of experts in the history of the Ming Dynasty, a textile industry executive, economist experts in the textile industry, and a Ming Dynasty history scholar. The research instrument was a semi-structured interview, analyzing the internal and external environmental factors of the textile industry. From the interviews, it was found that there were external and internal factors affecting the management of the Ming Dynasty textile industry. The external factors included the land system, household registration system, craftsman system, tax system, trade system and clothing styles. The internal factors were the internal components of the textile industry, which included raw materials, craftsmen, textile equipment and textile products, which can be used as a guideline for the management of the Ming Dynasty textile industry to adapt to the growth of the global economy.